CFD-based thermal limit prediction of LiFePO4 submarine battery modules using UDF heat generation and hybrid cooling - Fajri Narotama; Prabowo Prabowo (Jurnal Polimesin, 2026)
This study investigates the transient thermal behavior of LiFePO4 battery modules in a diesel-electric submarine battery compartment under constant 1C and 1.4C discharge conditions. A three-dimensional CFD model was developed in ANSYS® Fluent, with conjugate heat transfer between the battery modules, the air domain, and the liquid cooling channels. Battery heat generation was calculated through a compiled User-Defined Function derived from an equivalent-circuit heat-generation formulation. The module was represented as a homogenized orthotropic solid, allowing the compartment-scale model to be solved without resolving each cell. The heat-source model was validated against published experimental data for a 100 Ah prismatic LFP cell, yielding an RMSE of 0.28°C and an MAE of 0.24°C. At 1C discharge, hybrid cooling reduced the final maximum temperature from 48.25 °C to 45.26°C, while both cooling configurations remained below the 50°C thermal cutoff. At 1.4C discharge, natural convection reached the cutoff at 2140 s, whereas hybrid cooling delayed it to 2403 s, extending the operating window by 263 s (12.3%). Although the reduction in final maximum temperature was limited, the average temperature decreased by 5.62°C. These results indicate that hybrid cooling mainly reduces global heat accumulation, while internal heat conduction remains the dominant factor governing local hotspot formation.